Polycystic ovary syndrome and recurrent pregnancy loss, a review of literature - Wartena, Rosa; Matjila, Mushi (Frontiers in Endocrinology, 2023)
Objective: PCOS is a syndrome of ovarian dysfunction associated with recurrent pregnancy loss. Several correlating factors have been investigated that influence the risk of pregnancy loss in PCOS. However, uncertainty remains about their contribution to pregnancy loss and prognosis. This review of literature aims to identify what is known and what requires further investigation on the relationship between PCOS and recurrent pregnancy loss, to guide future research and optimize medical guidance throughout pregnancy. Study design: a review of literature was performed on several search engines using the following terms; polycystic ovarian syndrome, PCOS, recurrent pregnancy loss, recurrent miscarriage, RPL, aborted fetus, abortus provocatus, miscarriage and habitual abortion. Results: 37 articles were included; 3 systematic reviews, 1 meta-analysis, 2 randomized controlled trials, 6 prospective cohort studies, 22 case-control studies and 3 case series. The main objectives investigated by studies were pregnancy complications, pregnancy loss and live birth in the PCOS population. Conclusion: Studies that investigated the relationship between PCOS and recurrent pregnancy loss are few and inconsistent and warrant further research. Factors apt for further investigation include the extent to which PCOS phenotypes, BMI, obesity, insulin resistance, hyperandrogenemia, SHBG, hs-CRP, CTRP6, adiponectin, plasma leptin, homocysteine, AMH and thrombophilia contribute to further risk of miscarriage. Other factors requiring further exploration in relation to risk for miscarriage in PCOS patient with RPL include sOB-R, PAI-Fx and the Factor-V-Leiden mutations.